Poisoned arrows and flames of grace: Emotions inside and outside in Felix's Life of St Guthlac and the Old English prose Life of St Guthlac - Jorgensen, Alice (Brepols, 2025)
Where is emotion? The most influential study of emotion concepts in pre-Conquest England, Leslie Lockett’s justly celebrated Anglo-Saxon Psychologies in the Vernacular and Latin Traditions, starts by outlining the ‘hydraulic model’ of emotion as pressure, surging, and temperature change inside the heart or breast.
CULTURAL MODELS FOR EMOTIONS IN THE NORTH ATLANTIC VERNACULARS, 700-1400
PUBLISHED
Turnhout
Keywords: Identities in Transformation; Anglo-Latin; EMOTION; EMOTIONS; Old English; Old English prose; hagiography; History; Literature